Book Review of "How to do Linguistics with R – Data Exploration and Statistical Analysis". (7th December 2016) - Calude, Andreea
Abstract : How to do Linguistics with R – Data Exploration and Statistical Analysis NATALIA LEVSHINA Amsterdam: John Benjamins, 2015, 443 pp.